The Teixeira Leite sisters and their transatlantic alliances: rebuilding an elite social network from the French Third Republic (1880-1930) - Cecília Elisabeth Barbosa Soares (Anais do Museu Paulista: História e Cultura Material)
This article partially rebuilds the social network of Brazilian businesswoman Eufrásia Teixeira Leite (1850-1930) and her sister Francisca (1845-1899), by analyzing a sample of letters, cards, and telegram received by her at different periods of her lifetime. A comprehensive methodology used primary sources, such as correspondence and other documents of Eufrásia’s personal archive, complementary to secondary sources, to identify her interlocutors and, indirectly, explore the personality and interests of a 19th century liberal woman. The results illustrate the role of storytelling in sociohistorical research and women’s studies, based on individual cases and using personal archives as a starting point for a broader analysis.